Bare the Black Mildew - Histomorphological Study of Fungi in Vicinity and Fungi in Tissue Biopsies of Mucormycosis - Nandini Hasilkar; P Shashikala; K Rajashree (Journal of Medical Sciences and Health, 2023)
Introduction: The “Black fungus” epidemic hitting COVID - 19 patients has led to a scare among general public and inquisitiveness among medical fraternity about the probable source of this fungus. A wide range of fungi are seen in and around our vicinity especially growing on kitchen items like vegetables, fruits, other organic materials, etc. Hence, an attempt was made to study the morphology of these fungi and compare it with the morphology of fungi observed in tissue biopsies sent routinely. Objectives: 1. To study the morphology of fungi that grow in close vicinity especially food items. 2. To compare morphology of same with fungi that are identified in patient samples. Methodology: This is a cross-sectional study done in the Department of Pathology. Various fungi grown on vegetables, food, fruits and in the vicinity were included. Representative bits from these were fixed in 10% formalin and processed routinely. H and E sections were studied for morphology of the fungus under light microscopy. These were compared with the tissue biopsies of patients with fungal infection. Results: Thirty samples were processed (15 vegetables, 7 fruits, 5 organic materials, 3 plants). On morphological comparison of Group A with Group B, only aspergillus and candida appeared simila. Other details are discussed. Conclusion: Exposure to contaminated fruits, vegetables and other environmental materials maybe a risk for development of fungal infections in people with already existing co-morbidities/compromised immunity. Novelty: Attempt to explore common sources of fungi in our vicinity. Keywords: Black fungus, Fungi, Morphology of fungi, COVID19 pandemic, COVID, Fruits, Vegetables, Environment